2016
DOI: 10.1128/jvi.03023-15
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Herpes Simplex Virus 1 pUS9 in Virus Anterograde Axonal Transport and Final Assembly in Growth Cones in Distal Axons

Abstract: The herpes simplex virus type 1 (HSV-1) envelope protein pUS9 plays an important role in virus anterograde axonal transport and spread from neuronal axons. In this study, we used both confocal microscopy and transmission electron microscopy (TEM) to examine the role of pUS9 in the anterograde transport and assembly of HSV-1 in the distal axon of human and rat dorsal root ganglion (DRG) neurons using US9 deletion (US9 ؊ ), repair (US9R), and wild-type (strain F, 17, and KOS) viruses. Using confocal microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
1
22
1
Order By: Relevance
“…Similar observations have been reported for an HSV-1 pUS9 full deletion mutant (11). Our current findings with the three-chamber system using an HSV-1 pUS9 basic domain mutant also are similar to our observations with a complete deletion of pUS9 (53). A role for HSV-1 gE/gI extracellular domains in contributing to both anterograde axonal transport and possibly also in the spread from distal axons to nonneuronal cells has been reported recently (14) and adds further support to the notion of redundancy in transport processes essential for viral replication (49).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Similar observations have been reported for an HSV-1 pUS9 full deletion mutant (11). Our current findings with the three-chamber system using an HSV-1 pUS9 basic domain mutant also are similar to our observations with a complete deletion of pUS9 (53). A role for HSV-1 gE/gI extracellular domains in contributing to both anterograde axonal transport and possibly also in the spread from distal axons to nonneuronal cells has been reported recently (14) and adds further support to the notion of redundancy in transport processes essential for viral replication (49).…”
Section: Discussionsupporting
confidence: 81%
“…The fact there is no obvious axonal transport phenotype reported for KOS in animal models (46) may be due to the presence of compensating mutations, such as an observed extension of the C-terminal end of pUS8A (44,45). However, we have observed a neuronal spread defect for KOS in vitro using dissociated rat DRG neurons (53). In the case of McIntyre, another mutation of note is a frameshift mutation which results in an extension of the C-terminal tail of gI (43), which, along with truncated pUS9, may contribute rat DRG neurons were dissociated, pelleted through a 35% Percoll gradient, and plated into the somal compartment of three-chamber microfluidic devices.…”
Section: Discussioncontrasting
confidence: 44%
“…PRV US9 binds to a kinesin-3 protein, KIF1A (15), and the HSV US9 and US11 proteins bind kinesin-1 proteins in pulldown experiments (22,26). It was also suggested that HSV US9-null mutants have defects during anterograde transport, i.e., after virus entry into axons (39). However, our studies of both gE Ϫ and US9 Ϫ single mutants and gE Ϫ US9 Ϫ double mutants produced different conclusions: once HSV capsids or virions enter axons, their transport is normal, the kinetics of transport are not different from those for wild-type HSV, and there is no increased stalling (17).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have proposed a role for US9p in HSV-1 capsid envelopment in human and rat DRGs. In that case, the envelopment defect was interpreted to be in neuronal growth cones and varicosities, following axonal transport of naked capsids to those locations in accord with the separate model ( Figure 4) [202].…”
Section: Molecular Roles For Ge/gi and Us9p In Anterograde Transport mentioning
confidence: 77%
“…Compared to wild type controls, HSV-1 mutants lacking gE or gI (thus in both cases functionally null for the gE/gI heterodimer) or the US9 gene showed 50%-75% fewer naked capsids and viral glycoprotein-associated structures entering the axons of human SK-N-SH neurons, though transport of capsids appeared more sensitive to the deletions than did transport of glycoproteins [188]. Loss of US9p similarly reduced the numbers of trafficking naked HSV-1 capsids by~50% in axons of human and rat DRGs [202] and essentially abolished it in axons of murine retinal ganglia [156], with more modest effects upon viral glycoprotein trafficking [156,188].…”
Section: Molecular Roles For Ge/gi and Us9p In Anterograde Transport mentioning
confidence: 99%